KETERLIBATAN ORANG TUA DALAM PENDAMPINGAN BELAJAR ANAK DI MASA PANDEMI COVID-19 - Hidayatu Sholihah; Yosafat Hermawan Trinugraha; Nurhadi Nurhadi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
This study intends to find out the involvement of parents in child learning assistance during the COVID-19 pandemic, the motives that influence parental involvement in child learning assistance, and determine the impact on children. This study uses the theory of symbolic interactionism expressed by Herbert Blummer. The method used is qualitative with an intrinsic case study approach. Data collection was carried out using interviews, observations, and documentation which were then tested for the validity of the data through triangulation of sources. Analysis of the data using the analysis scheme of Miles and Huberman. The results showed that the involvement of parents in assisting children's learning during the COVID-19 pandemic at MIM Mojorejo Nogosari, Boyolali Regency, namely providing opportunities for children to study independently and providing assistance during the learning process, conveying important and relevant insights according to children's learning needs. There are several factors that influence the willingness of parents to accompany their children to learn. The impact of parental involvement in child learning assistance during the COVID-19 pandemic is seen from 3 sectors, namely learning outcomes, understanding and mastery of learning materials, as well as changes in attitudes and personality.